Bank lending and macroprudential policies: Are Islamic banks differentially affected? - Abdulla Albinali (Islamic Economic Studies (IES), 2023)
Purpose - The purpose of the paper is to study the relevance of macroprudential policies (MPPs) in influencing bank lending in small open economies with dual banking systems. Design/methodology/approach - In the analysis, the author employed the dynamic panel data methodology as compared to alternate techniques since it is able to address potential endogeneity challenges. Findings - Using quarterly data from the period 2002-2020, the author finds that MPPs are highly effective in containing the growth of public credit, whereas its impact on private credit is much less effective. The disaggregated findings reveal that macroprudential measures are less effective in containing the growth of private credit by Islamic banks. Originality/value - The majority of studies on MPPs are focused on emerging and advanced economies, limiting their policy appeal from the standpoint of small open economies. In this connection, this paper contributes to the literature on the relevance of such policies for a small open economy with a dual banking system and significant hydrocarbon exports. The paper's analysis therefore holds relevance for similar economies, both in the region and elsewhere, on the role and relevance of MPPs with emphasis on Islamic banks.
Keywords: G21; G28; 330; Banking; Islamic; Macroprudential; Qatar